Epigenetic alterations in inflammatory bowel disease: the complex interplay between genome-wide methylation alterations, germline variation, and gene expression. (23rd February 2017) - Kalla, Rahul; Adams, Alex; Nimmo, Elaine; Kennedy, Nicholas; Ventham, Nicholas; Vatn, Morten; Jahnsen, Jorgen; Ricanek, Petr; Halfvarson, Jonas; Pierik, Marieke; Gomollon, Fernando; Gut, Ivo; et al.
Abstract: Background: Exploring DNA methylation in inflammatory bowel disease might provide an insight into the complex gene–environment interactions in disease pathogenesis. Our study aimed to characterise disease-associated methylation changes in newly diagnosed inflammatory bowel disease and explore its association with germline variation and gene expression. Methods: Samples were obtained from new onset inflammatory bowel disease in six European centres (IBD-Character project). Genome-wide methylation was measured (450k platform, Illumina, San Diego, CA, USA) in 641 whole blood DNA samples (298 controls, 150 Crohn's disease, 167 ulcerative colitis, 26 inflammatory bowel disease unclassified). Genotyping and gene expression were performed using HumanOmniExpressExome-8 BeadChips (Illumina) and Ion AmpliSeq (ThermoFisher, Waltham, MA, USA) platforms, respectively. Correlation and pathway analyses were performed between the top differentially methylated regions and gene expression. Findings: M195 probes exhibited Holm-significant inflammatory bowel disease-associated methylation differences, including MIR21 (p=3·7 × 10 − 20 ) and RPS6KA2 (p=1·1 × 10 −19 ) with only one probe differentiating Crohn's disease from ulcerative colitis ( NAV2, p=6·82 × 10 −8 ). Paired genetic and methylation data showed 1037 significant methylation quantitative trait loci indicating a genetic influence on several key loci: RPS6KA2 (p=8·6 × 10 −34 ) and MIR21 (rs8078424, p=4·4 × 10 − 25 ; rs10853015, p=7·4 × 10 −21 ). 1543 differentially methylated regions (DMRs) were identified and included MIR21, RPS6KA2, and TNF . These DMRs mapped to 8214 mRNA profiles of which 1916 showed Holm-significant correlation with methylation such as IL32 (seven probes: r =–0·50 to −0·66, p=6·0 × 10 −76 ). GO term analyses of these highly correlated genes revealed pathways that regulate cell–cell adhesion and immune cell differentiation. Interpretation: Our data provide a comprehensive multicentre genome-wide profile of the circulating methylome and give an insight into the complex interplay between differential methylation, germline variation, and gene expression in immune mediated disease. Funding: RK and AA are funded by IBD-Character (a European Union 7th Framework Programme project).